2018
DOI: 10.17557/tjfc.484975
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Genetic Diversity of Cotton Breeding Programs in Venezuela

Abstract: There is a steady increase of demands for textile crops, where cotton is the most popular natural fiber, therefore, it is necessary to exploit cotton genetic resources. In order to develop and improve crop populations, a cotton breeding program requires access to new sources of germplasm. With the objectives to evaluate the productivity of local and introduced genotypes from Syria and Brazil, and to expand the genetic base in the Venezuelan Cotton Breeding Program, 16 genotypes were evaluated at three location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…For both genotypes, LP values decreased significantly at 142,857 pl ha −1 , however LP values were not more inferior than 38%, which is the textile industry requirement in Venezuela. In this study, LP values were high, as compared with other studies carried out in similar environments [6,7]. In these cases plants were planted at 62,500 pl ha −1 and followed the same pattern as reported by McCarty et al [31], where LP become higher as plant population increased.…”
Section: Ly (Kg Hasupporting
confidence: 85%
See 1 more Smart Citation
“…For both genotypes, LP values decreased significantly at 142,857 pl ha −1 , however LP values were not more inferior than 38%, which is the textile industry requirement in Venezuela. In this study, LP values were high, as compared with other studies carried out in similar environments [6,7]. In these cases plants were planted at 62,500 pl ha −1 and followed the same pattern as reported by McCarty et al [31], where LP become higher as plant population increased.…”
Section: Ly (Kg Hasupporting
confidence: 85%
“…In Venezuela, different studies have focused on the identification of foreign varieties or those developed in the national cotton breeding program of INIA (Instituto Nacional de Investigaciones Agropecuarias) that are adapted to specific edaphic and climatic conditions, maximizing expression of Agronomy 2019, 9, 349 2 of 9 fiber yield and quality [5][6][7]. These studies have been developed based on spatial arrangement less than or equal to 62,500 pl ha −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the second greatest contribution to total variation was observed from L (19%), indicating that the locations tested were representative to obtain good estimates of genetic prog ress. Similar effects in G, E, and G x E interactions were reported for LY, its components, and agronomic traits under similar tropical conditions (Farias et al., 2016; Gonzalez et al., 2007; Guzman et al., 2018).…”
Section: Resultssupporting
confidence: 65%